2007
DOI: 10.1038/sj.cdd.4402233
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces autophagic cell death independent of apoptosis in transformed and cancer cells

Abstract: Autophagy is a self-digestion process that degrades intracellular structures in response to stresses leading to cell survival. When autophagy is prolonged, this could lead to cell death. Generation of reactive oxygen species (ROS) through oxidative stress causes cell death. The role of autophagy in oxidative stress-induced cell death is unknown. In this study, we report that two ROS-generating agents, hydrogen peroxide (H 2 O 2 ) and 2-methoxyestradiol (2-ME), induced autophagy in the transformed cell line HEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
461
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 626 publications
(495 citation statements)
references
References 38 publications
15
461
2
4
Order By: Relevance
“…Again, the loss of the cellular synthesis ability at 24 h was manifested under all the studied conditions. Autophagy triggered by oxidative stress has been amply documented in transformed and cancer cells (Chen et al, 2008), although the relationship between psychological and/ or physical stress and autophagy is still unknown. Recently, our group showed that autophagy may be directly related to the oxidative stress status of the muscle cells in beef (García-Macia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Again, the loss of the cellular synthesis ability at 24 h was manifested under all the studied conditions. Autophagy triggered by oxidative stress has been amply documented in transformed and cancer cells (Chen et al, 2008), although the relationship between psychological and/ or physical stress and autophagy is still unknown. Recently, our group showed that autophagy may be directly related to the oxidative stress status of the muscle cells in beef (García-Macia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy clears depolarized mitochondria to reduce the excessive production of ROS by increasing BECN1 or regulating ATG4 activity [26,27] , which is protective in MS.…”
Section: Autophagy and Mitochondria In Msmentioning
confidence: 99%
“…In MS, the decreased expression of cytochrome c oxidase subunit 5b may impair the function of mitochondria [24] . Dysfunction of mitochondria produces reactive oxygen species (ROS), which contribute to demyelination and axonal loss [25] .Autophagy clears depolarized mitochondria to reduce the excessive production of ROS by increasing BECN1 or regulating ATG4 activity [26,27] , which is protective in MS. …”
mentioning
confidence: 99%
“…36 ROS are associated with different types of cell death mechanisms (classical apoptosis, necrosis and autophagy). [38][39][40][41][42][43] CD40 stimulation induced an almost twofold increase in basal ROS production when compared with unstimulated CLL cells. (Figures 6a and b left panel, 3T40 medium versus 3T3 medium).…”
Section: Rituximab-mediated Death Of Cd40-stimulated Cll Cells Is Ca mentioning
confidence: 99%